Analysis of CA content and CPSF6 dependence of early HIV-1 replication complexes in SupT1-R5 cells - Zila, Vojtech; Müller, Thorsten G.; Laketa, Vibor; Müller, Barbara; Kräusslich, Hans-Georg (mBio, 2019)
HIV-1 infects host cells by fusion at the plasma membrane, leading to cytoplasmic entry of the viral capsid encasing the genome and replication machinery. The capsid eventually needs to disassemble, but time and location of uncoating are not fully characterized and may vary depending on the host cell. To study the fate of the capsid by fluorescence and superresolution (STED) microscopy, we established an experimental system that allows discrimination of subviral structures in the cytosol from intact virions at the plasma membrane or in endosomes without genetic modification of the virus. Quantitative microscopy of infected SupT1-R5 cells revealed that the CA signal on cytosolic HIV-1 complexes corresponded to ∼50% of that found in virions at the cell surface, in agreement with dissociation of nonassembled CA molecules from entering capsids after membrane fusion. The relative amount of CA in postfusion complexes remained stable until they reached the nuclear pore complex, while subviral structures in the nucleus of infected cells lacked detectable CA. An HIV-1 variant defective in binding of the host protein cleavage and polyadenylation specificity factor 6 (CPSF6) exhibited accumulation of CA-positive subviral complexes close to the nuclear envelope without loss of infectivity; STED microscopy revealed direct association of these complexes with nuclear pores. These results support previous observations indicating capsid uncoating at the nuclear pore in infected T-cell lines. They suggest that largely intact HIV-1 capsids dock at the nuclear pore in infected SupT1-R5 cells, with CPSF6 being a facilitator of nucleoplasmic entry in this cell type, as has been observed for infected macrophages. - IMPORTANCE The HIV-1 capsid performs essential functions during early viral replication and is an interesting target for novel antivirals. Thus, understanding molecular and structural details of capsid function will be important for elucidating early HIV-1 (and retroviral in general) replication in relevant target cells and may also aid antiviral development. Here, we show that HIV-1 capsids stay largely intact during transport to the nucleus of infected T cells but appear to uncoat upon entry into the nucleoplasm. These results support the hypothesis that capsids protect the HIV-1 genome from cytoplasmic defense mechanisms and target the genome toward the nucleus. A protective role of the capsid could be a paradigm that also applies to other viruses. Our findings raise the question of how reverse transcription of the HIV-1 genome is accomplished in the context of the capsid structure and whether the process is completed before the capsid is uncoated at the nuclear pore.
Gesehen am 14.01.2020